Cetrorelix in reproductive medicine - Sebastian Findeklee, M.D., Ph.D; Prof Klaus Diedrich (Elsevier, 2023)
This book chapter presents the most important clinical aspects concerning the gonadotropin-releasing hormone antagonist cetrorelix and its importance in reproductive medicine. After an overview of the historical milestones in the development and establishment of cetrorelix in the context of ovarian stimulation treatment, its dosage, effects, and side effects are evaluated. The chapter terminates with a conclusion emphasizing the ease of use and the increase in patient safety because of a significantly reduced risk of ovarian hyperstimulation syndrome with cetrorelix compared with the agonist protocol